Analysis of an accessibility strategy for deaf people: Videos on a traveling science center - Ferreira, Alessandra Teles Sirvinskas; Alves, Gustavo Henrique Varela Saturnino; Vasconcelos, Iara Alves Hooper; Souza, Thaís Varandas de Azeredo; Fragel-Madeira, Lucianne (Frontiers in Education, 2023)
Brazilian traveling science centers have difficulties in providing sign language accessibility to the deaf public that visits them. This study's main objective is to analyze the contribution of accessible video guides in Brazilian Sign Language (BSL) in helping deaf visitors understand the activities proposed by the traveling science center “Ciências Sob Tendas”. This research used a critical quali-quantitative approach, that involved 128 deaf students from middle and high school. Data was gathered via online survey and video recording. Results indicate a successful use of the video guides by the deaf public. Within this specific research which 745 questionnaires were answered, we identified that the videos, along with interactive activities, contributed to the interest, curiosity, and understanding of the themes presented. Furthermore, the return of deaf people to visit activities second and third time may indicate the potential of this science communication strategy to stimulate their interest in scientific knowledge. However, 15% of responses showed that they had some difficulty in understanding the videos explanation. This may indicate that, although videos are a well-accepted alternative for accessibility, the presence of an interpreter guide or a deaf guide, when possible, is ideal. After all, a professional interpreter can adjust the speech to make themselves understood. Thus, we consider that accessible video guides in BSL are a viable resource for providing accessibility to the deaf people in traveling science centers.